Real Private Industrial Sector and Role in Comprehension the Labor Force of Iraq to (1990-2009) - عباس, وليد عبد المنعم; حسين, مهند علي (Journal of Economics and Administrative Sciences, 2013)
At different stages of the evolution of the modern Iraqi state ears last century did not receive the industrial sectors importance in  great domestic production (GDP) and  that the limited  resources available in the initial stage and the dominance of public sector industry in the late stage , so the continued decline in the contribution  of the private industrial sector in  GDP , and this is why imbalance in the labor market and reduced  demand for manpower in this sector despite the high rates of labor supply and the various skills and levels of investments, their human  and the different geographical distribution , and direction of labor to other economic sectors most  requested of the labor force such as the pubic sector and service sector, as well as the relationship of  positive large between output  and demand for labor that did not play its due to poor performance of the output in this sector, which led to double the impact in this sector to attract employment .  Different working conditions and incentives and orientations between both the industrial and public sectors was reflected later on the efficiency of human resources and productivity delete facilities nationalized long experience of investment and production could not be compensated under the bureaucratic public sector, also lost direction totalitarian economic policies previous all elements of economic efficiency and competitiveness of production, than about the Iraqi economy to yield economy depends on oil revenues, without being able to these policies create growth parallel in the Iraqi economy, and that the administration of socialism and the predominance of the public sector has been marginalized private sector and disrupted its role in development, this marginalization has led to decline the role of the private industrial sector and the size of its ability to develop and absorb the workforce, particularly that sector limited the capabilities and expertise, which dominated the activity of this sector work small and medium enterprises, which contributed modestly in the composition of GDP due to the weak capacity of physical and technical